Analisis Sifat Fisik dan Mekanik Paving Block dengan Penambahan Plastik dan Crumb Rubber - Benigno Faza Akbari; Muhammad Aufa Ahda Athoillah; Juny Andry Sulistyo (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Paving blocks are construction materials made from a mixture of cement, sand, aggregate, and water. Typically, paving blocks are molded in square or rectangular shapes and are used as surface coverings for roads, sidewalks, parking lots, and other public areas. One of the reasons why paving blocks are popular is because of their load-bearing ability, durability, and aesthetic appearance. This research aims to analyze paving blocks used in construction. Another objective of the research conducted was to analyze the opportunity of using added materials, namely recycled plastic and crumb rubber in making paving blocks, which aims to produce quality and sustainable products. In experimental research, the first step is to determine the variation in the composition of the additives used. Next, paving blocks are made through a dry mixing process until they are homogeneous, then molded using hexagonal molds and compacted manually. After that, the test objects undergo a curing process for 28 days before testing. Testing of paving blocks includes compressive strength and water absorption tests to determine the effect of adding additives on the quality and performance of the modified paving blocks. The results showed that the addition of plastic and crumb rubber can increase the strength of paving blocks and ensure flexibility and the product itself, reduce production costs and effective use of industrial waste.